Reliability performance for dynamic multi-state repairable systems with K regimes - Shen, Jingyuan; Cui, Lirong (IIE transactions, 2017)
It is well known that many factors can influence the rate at which a machine degrades. In this article, we study a multi-state repairable system subject to continuous degradation and dynamically evolving regimes. The degradation rate of the system depends not only on the system states but also on the regimes driven by the varying external environments. Movements between the system states are governed by continuous-time Markov processes but with different transition rate matrices due to different regimes; meanwhile, the evolution of regime is also governed by a Markov process. Such a system can be developed by the Markov regime-switching model. To derive the system performance such as the first passage time distribution, a Markov renewal process is introduced by giving its semi-Markov kernel. We also consider the system in the context of periodic inspections and maintenance and give the limiting average availability. Finally, some numerical examples are given to demonstrate and validate the proposed framework.